Red Hat Linux 6 - Davis, Harold, 1953- (Visual quickpro guide., 1999)
CD-ROM includes Red Hat Linux 6.0 Publisher's Edition (Linux kernel version 2.22-15), GNOME, KDE 1.1, Netscape Communicator 4.5.1, the GLMP (GNU Image Manipulation Program) 1.04, plus games, customization applications, utilities, etc.